2016
DOI: 10.1016/s1556-0864(16)30171-x
|View full text |Cite
|
Sign up to set email alerts
|

57O Efficacy, safety and tolerability of MEDI4736 (durvalumab [D]), a human IgG1 anti-programmed cell death-ligand-1 (PD-L1) antibody, combined with gefitinib (G): A phase I expansion in TKI-naïve patients (pts) with EGFR mutant NSCLC

Abstract: Translational research 57O Efficacy, safety and tolerability of MEDI4736 (durvalumab [D]), a human IgG1 antiprogrammed cell death-ligand-1 (PD-L1) antibody, combined with gefitinib (G): A phase I expansion in TKI-naïve patients (pts) with EGFR mutant NSCLC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 0 publications
5
75
0
Order By: Relevance
“…On the other hand, Ahn et al (9) reported that ILD was observed in 38% of cases receiving combination treatment with osimertinib and durvalumab, a PD-L1 inhibitor, which suggests that treatment with such a drug combination may dramatically increase the risk of ILD. Notably, a similar increased risk of ILD has not been reported for combination treatment with durvalumab and gefitinib (10). These studies suggest that previous treatment with nivolumab may affect the onset of ILD during osimertinib treatment.…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, Ahn et al (9) reported that ILD was observed in 38% of cases receiving combination treatment with osimertinib and durvalumab, a PD-L1 inhibitor, which suggests that treatment with such a drug combination may dramatically increase the risk of ILD. Notably, a similar increased risk of ILD has not been reported for combination treatment with durvalumab and gefitinib (10). These studies suggest that previous treatment with nivolumab may affect the onset of ILD during osimertinib treatment.…”
Section: Discussionsupporting
confidence: 63%
“…gov number NCT02454933) evaluating the combination of durvalumab with osimertinib compared to osimertinib alone in patients with T790M positive NSCLC following a prior EGFR TKI has been also suspended. Similarly to the TATTON study, another phase I open-label multicenter study (ClinicalTrials.gov number NCT02088112) was initiated to evaluate durvalumab in combination with gefitinib as first line therapy in EGFR mutant NSCLC and the expansion phase data have been reported (34). No clinically relevant differences in the objective response rate (79%) compared to what is already known for gefitinib monotherapy (73.7%) (55) in this setting were observed ( Table 2).…”
Section: Introductionmentioning
confidence: 97%
“…No clinically relevant differences in the objective response rate (79%) compared to what is already known for gefitinib monotherapy (73.7%) (55) in this setting were observed ( Table 2). Overall 55% of the patients suffered grade 3 adverse events and treatment discontinuation due to adverse events was reported in 20% of the patients (34).…”
Section: Introductionmentioning
confidence: 99%
“…High rates of grade 3/4 treatment related toxicity (55%) was also reported in a phase I study of durvalumab and gefitinib (18). The combination of erlotinib with atezolizumab reported an ORR of 75% and disease control rate of 95%, with 39% grade 3/4 adverse events (19).…”
mentioning
confidence: 65%